Interferometric and dual beam observations of daytime spread-F-like irregularities over Jicamarca - Chau Chong Shing, Jorge Luis (2001)
We report new observations made on April 11 2000 over Jicamarca of daytime spread-F-like irregularities. These irregularities are extremely rare (this was the fourth observation in the history of Jicamarca) and were first reported by Woodman et al. [1985]. The main features of these new observations, which are similar to the previous ones, are that they were: (1) two orders of magnitude stronger than the incoherent scatter echoes at the F peak, (2) observed between 1400 and 1600 LT; (3) characterized by small Doppler shifts (vd < 1 m s-1); and (4) characterized by long correlation times, i.e., narrow spectral widths. The latter is interpreted as evidence that these irregularities are field aligned (very aspect sensitive in the north-south direction). On this occasion the irregularities occurred at higher altitudes than before, between 950 and 1450 km compared to 600-1000 km. The echoes in these recent observations were quite localized in the east-west direction (they were much stronger in the west beam than in the east beam). Furthermore, using interferometry we determined that the echoes were aspect sensitive in the east-west (as well as north-south) direction with aspect angle widths as small as 0.2 degrees, particularly when the echoes were strong.